Planning in Ciskei secondary schools with special reference to managerial teams - Magqaza, Ocean Bungani (Rhodes University, Faculty of Education, Department of Education, 1994)
Educational leadership and management is a very wide field of study with interdependent components that should form a chain reaction in order to bring about effective management. This study attempts to investigate planning in schools which is one of the educational leadership and management components or functions. Very little research work has been done on educational planning in the Ciskei schools. This is a shortcoming since the number of secondary schools has mushroomed in the late twentieth century. The Ciskei educational managers and parents need to know and take note of the possible situations in the various schools. This is opportune time, particularly that recent events, i.e. students' demands and strikes, are drawing parents closer to the education of their children. The researcher's experience of inspecting school administration since 1990 has reinforced his conviction that the managerial teams in the Ciskei secondary schools have little knowledge of management, and of planning in particular. Although the investigation is into secondary school administration, it is also pertinent to primary school planning. Management, i.e. school year-planning, control of work, staff development, appointment of teachers, policy governing students and teachers are discussed at length . Joint planning, i.e. a participative or consultative approach, and advance planning, are investigated in relation to the school year-programme. The existence of statutory bodies in the various schools is assessed in order to test parents' involvement in the education of their children. School tours are discussed in relation to students' involvement in the school activities. The analysis of the results highlights areas that require attention, and the recommendations given address the controversial issues in planning in the various schools.
Keywords: Curriculum planning -- South Africa -- Ciskei; Educational planning -- South Africa -- Ciskei; Teaching teams; School management and organization